Gender Affirming Medical Treatment Desire and Treatment Motives in Binary and Non-Binary Transgender Individuals. Issue 7 (10th April 2022) - Kennis, Mathilde; Duecker, Felix; T'Sjoen, Guy; Sack, Alexander T.; Dewitte, Marieke
ABSTRACT: Background: It is currently unknown whether there are differences in desire for gender affirming medical treatment (GAMT) between binary and non-binary transgender individuals, although the latter seek treatment less prevalently. Aim: To investigate differences between binary and non-binary individuals on received GAMT, desire for GAMT, and motives for (not) wanting GAMT, and to explore the association between having an unfulfilled treatment desire and general and sexual well-being. Methods: We conducted an online questionnaire in a community sample of 125 transgender men, 72 transgender women, and 62 non-binary transgender individuals (age: M = 30.4, SD = 11.31, range 18-69). Outcome measures: Undergone GAMT, GAMT desire, motives for (not) wanting (further) GAMT, Utrecht Gender Dysphoria Scale, Satisfaction With Life Scale, Hospital Anxiety and Depression Scale, Global Measure of Sexual Satisfaction, transgender-specific body image worries, and sexual self-concept discrepancies. Results: Binary transgender participants reported having undergone more GAMT procedures than non-binary transgender participants ( P < .001 for both gender affirming hormone treatment (GAHT) and gender affirming surgery (GAS)). While binary participants reported a stronger desire for GAHT compared to non-binary participants ( X 2 (1, N = 93) = 32.63, P < .001), the groups did not differ in their desire for GAS ( X 2 (1, N = 247) = 0.68, P = .411). Binary and non-binary participants reported similar reasons for wanting treatment, mostly related to body and/or gender incongruence and gender affirmation. In terms of not wanting treatment, the non-binary group reported their gender identity as the most important reason, while the binary group mostly mentioned possible medical complications. The majority of both groups had an unfulfilled treatment desire (69% of binary participants and 64.5% of non-binary participants), which was related to lower levels of general life satisfaction ( P < .001) and sexual satisfaction ( P = .005), more anxiety ( P = .006) and transgender-specific body image worries ( P < .001), and larger sexual self-concept discrepancies ( P < .001 for actual and/or ideal, P < .001 for actual and/or ought). Clinical implications: Systemic barriers to GAMT (especially GAS) should be removed not only for binary but also for non-binary identifying transgender individuals to decrease the discrepancy between treatment desire and actually seeking treatment. Strengths & limitations: This study was the first to systematically investigate differences in treatment desire motives between binary and non-binary transgender individuals, while also showing the possible negative consequences of an unfulfilled treatment desire. Given the online character of the study, results may not generalize to the broader transgender community. Conclusion: Similarly to binary transgender individuals, many non-binary transgender individuals have a desire for GAMT, and not being able to receive GAMT has a negative effect on their mental and sexual health. Further efforts should be made to make GAMT accessible for all transgender individuals, regardless of gender identity.